Capillary Blood for Prostate-specific Antigen Testing: The PSA-CAP Study - Martin Wallisch; Peter Albers; Nikolaus Becker; Friedrich Boege; Derik Hermsen; Tanmay Ramesh Londhe; Jale Lakes; Jan Philipp Radtke; Agne Krilaviciute; Petra Seibold; Axel Benner; Maral Saadati; et al. (European Urology Open Science, 2025)
Risk-adapted prostate cancer (PC) screening is currently based on a combination of prostate-specific antigen (PSA) testing, risk assessment, and magnetic resonance imaging (MRI). Classical venous blood sampling is usually performed by health care professionals, which may reduce participation in future population-based screening programmes due to limited resources. The PSA-CAP study (NCT06626386) evaluated the feasibility of using capillary blood from fingertip sampling compared with venous blood for PSA determination, in order to facilitate access for PSA testing. This prospective study analysed 196 men aged 40–75 yr. PSA levels were measured from both capillary and venous blood using the same analytical method. The stability of samples stored at room temperature was assessed over a week. Discomfort associated with both collection methods was evaluated using a numerical pain scale. No significant differences were found between capillary and venous PSA measurements. Samples remained stable up to 7 d without immediate centrifugation. Pain scores for capillary (1.52/10) and venous (1.61/10) collections were generally low and not significantly different (p = 0.27). Four cases had insufficient capillary blood for an analysis, and two outliers were resolved upon retesting. Capillary blood sampling is a viable alternative to venous puncture for PSA measurement, offering the same level of accuracy and stability with no difference in discomfort. This approach could enhance participation rates in future PC screening programmes. Patient summary: We studied an alternative method of blood collection to measure prostate-specific antigen level, a key test for prostate cancer risk, using fingertip sampling instead of venous blood. The results were comparable with and as stable as those from venous blood collection, with similar comfort levels. This technique may simplify future prostate cancer screening programmes and could lead to a higher acceptance rate.